Non-intubated anaesthetic technique in open bilobectomy in a patient with severely impaired lung function - Szabó Zsolt; Tánczos Tamás; Lebák Gábor; Molnár Zsolt; Furák József (2018)
General anaesthesia has been the most commonly used method for almost all types of thoracic surgery. Recently, there has been a growing interest in non-intubated anaesthetic techniques. The rationale being, to prevent complications related to general anaesthesia and positive pressure ventilation such as barotrauma or ventilation-perfusion mismatch. We present a case with severely impaired forced expiration volume (26%), carbon monoxide diffusing capacity (26%) and VO2max (13.9 mL/kg/min). According to current guidelines, this patient was suitable to undergo one-lung ventilation only with high risk of morbidity and mortality. Therefore, we chose the non-intubated technique for thoracotomy. Oxygenation was satisfactory throughout, the patient remained hemodynamically stable and the operation was uneventful. Oxygen supplementation was stopped from day 2 and he was discharged on day 7. To our knowledge, this is the first case report where a planned non-intubated method was applied for thoracotomy, and our results suggest that it might be a feasible and safe approach for open thoracotomy in difficult cases where severely impaired lung function indicates that one lung ventilation may carry significant risks.